Types, levels and causes of post-harvest milk and dairy losses in sub-Saharan Africa and the Near East: Phase two synthesis report - Lore, Tezira A.; Omore, Amos O.; Staal, Steven J. (International Livestock Research Institute, 2005)
The following is a synthesis report highlighting the results of rapid appraisals aimed at characterizing post-harvest milk and dairy losses in Ethiopia, Kenya, Syria, Tanzania and Uganda. In Kenya, Uganda and Tanzania, the rapid appraisals were undertaken during the dry month of July 2003, when milk yields were relatively low in the region1. Post-harvest milk losses have been quantified both in terms of quantity and monetary value lost. Specific links in the milk chain where significant losses are experienced, and those losses that have pragmatic solutions have been identified and targeted for appropriate interventions aimed at reducing or eliminating the losses. Key findings showed that most post-harvest milk losses are experienced in the small-scale informal dairy sector; formal milk processors generally incur minimal losses. In terms of quantity, significant milk losses occur at the farm level (8.4, 28.6, 46.4 and 54.2 million litres of milk per year for Uganda, Ethiopia, Tanzania and Kenya, respectively) valued at approximately 0.9–11 million US dollars. Post-harvest losses of milk at the farm represented 1.3 to 6.4 percent of the value of available milk at the farm level. Poor road infrastructure and inadequate markets for raw milk are the main causes of farm-level losses, which are largely in form of spoilage, spillage, and “forced home consumption” (including by calves and humans) over and above normal household consumption. Although in quantity terms forced losses may seem to be high, in value terms they are less significant, because an estimated 70% of the value of the milk is still captured. Along the marketing chain, milk loss is mainly due to spillage and spoilage. These losses are occasioned by poor access to markets, poor milk handling practices as well as irregular power supply in milk processing plants. Based on the dry season rapid appraisal data, the total value of post-harvest milk losses per year amounted 9.9, 14.2, 17.8 and 23.9 million US dollars for Tanzania, Ethiopia, Kenya and Uganda, respectively. Recommendations for interventions aimed at reducing milk losses have been targeted at the farm level and small-scale milk transporters. These are the two points in the chain where losses in value were found to be most significant. Four general areas of intervention are discussed: training, technology, policy/legislation and information. This report represents the first systematic attempt to accurately quantify postharvest milk losses in the countries studied. However, because of the small sample sizes, limited geographical coverage and the fact that the rapid appraisals were undertaken during the dry season only, the results obtained must be interpreted with caution, bearing in mind the limited scope of the study. Additionally, some of the data provided was not up to the standard required to make a complete valuation. Further comprehensive studies covering a wider scope are needed as a follow-up to the rapid appraisals in order to generate additional data on the levels of post-harvest milk and dairy losses at the national level and across seasons. Nevertheless, the information generated provides a useful basis for implementing the recommended interventions.